The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1017/s1049023x0003778x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Victims of Elder Abuse and Neglect: A Training Video for Prehospital Personnel

Abstract: Introduction:The majority of prehospital emergency medical services (EMS) personnel lack specific training relating to elder abuse and neglect.Objectives:To develop and test an audio visual training program that focuses on the identification and reporting of domestic violence in the elderly.Methods:A videotape was designed to be used as a 45-minute training course for prehospital personnel using one-half inch, super-VHS recording. A convenience sample of 60 EMS personnel working in Kent County then were asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…The 3-month post-training survey also indicated that paramedics did not routinely screen patients for domestic violence and only 31% were confident in asking questions regarding IPV. These results are similar to a study by Seamon et al 18 where 40% of 60 EMS personnel indicated they still were not confident enough to identify elder abuse following a 45-min training intervention. Continuing education and training seem central in improving pre-hospital provider's confidence and ability to identify IPV and warrants further investigation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The 3-month post-training survey also indicated that paramedics did not routinely screen patients for domestic violence and only 31% were confident in asking questions regarding IPV. These results are similar to a study by Seamon et al 18 where 40% of 60 EMS personnel indicated they still were not confident enough to identify elder abuse following a 45-min training intervention. Continuing education and training seem central in improving pre-hospital provider's confidence and ability to identify IPV and warrants further investigation.…”
Section: Discussionsupporting
confidence: 89%
“…2,8,10,18,20 Educational interventions were capable of increasing this knowledge, 2,5,8,18 but not necessarily the screening and reporting ability. 8,10,18 There was a relative paucity of information There has been no formal research performed within Australia regarding either knowledge, reporting ability or screening of IPV in the pre-hospital setting; that is ambulance officers and paramedics across Australia. Due to the differences in training, education and organisational structure of ambulance services worldwide, it is difficult to make comparisons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies examined the effectiveness of educational programs with professionals to detect, report or treat EAN with the majority finding short term positive outcomes (Jogerst et al 2008;Jogerst and Ely 1997;Seamon et al 1997;Uva and Guttman 1996;Liu et al 2010;Sugita and Garrett 2012). In the Jogerst et al (2008) study, increased training for APS investigators lead to more substantiations.…”
Section: Education For Professionals In Community Settingsmentioning
confidence: 99%
“…Participants rated their ability to diagnose elder abuse and assess the patient's home environment significantly higher than non-participants. In two different studies, education provided to emergency medical personnel also produced positive results in the recognition of abuse, including indicators of sexual abuse, and understanding correct reporting procedures (Seamon et al 1997;Uva and Guttman 1996). Another study tested a case management educational intervention with public health nurses through a cluster randomized controlled trial design; researchers found statistically significant differences between the intervention group that received educational sessions on case management, the process, and related practical activities in comparison to the control group (Liu et al 2010).…”
Section: Education For Professionals In Community Settingsmentioning
confidence: 99%